Bacterial glycosylation, it’s complicated - Szymanski, Christine M. (Frontiers in Molecular Biosciences, 2022)
Each microbe has the ability to produce a wide variety of sugar structures that includes some combination of glycolipids, glycoproteins, exopolysaccharides and oligosaccharides. For example, bacteria may synthesize lipooligosaccharides or lipopolysaccharides, teichoic and lipoteichoic acids, N- and O-linked glycoproteins, capsular polysaccharides, exopolysaccharides, poly-N-acetylglycosamine polymers, peptidoglycans, osmoregulated periplasmic glucans, trehalose or glycogen, just to name a few of the more broadly distributed carbohydrates that have been studied. The composition of many of these glycans are typically dissimilar from those described in eukaryotes, both in the seemingly endless repertoire of sugars that microbes are capable of synthesizing, and in the unique modifications that are attached to the carbohydrate residues. Furthermore, strain-to-strain differences in the carbohydrate building blocks used to create these glycoconjugates are the norm, and many strains possess additional mechanisms for turning on and off transferases that add specific monosaccharides and/or modifications, exponentially contributing to the structural heterogeneity observed by a single isolate, and preventing any structural generalization at the species level. In the past, a greater proportion of research effort was directed toward characterizing human pathogens rather than commensals or environmental isolates, and historically, the focus was on microbes that were simple to grow in large quantities and straightforward to genetically manipulate. These studies have revealed the complexity that exists among individual strains and have formed a foundation to better understand how other microbes, hosts and environments further transform the glycan composition of a single isolate. These studies also motivate researchers to further explore microbial glycan diversity, particularly as more sensitive analytical instruments and methods are developed to examine microbial populations in situ rather than in large scale from an enriched nutrient flask. This review emphasizes many of these points using the common foodborne pathogen Campylobacter jejuni as the model microbe.